Tubos de luz natural em habitação de interesse social - Santos, Gabriel de Sousa (2024)
Daylight brings psychophysiological benefits to users and self-construction can interfere with the availability of this resource in environments. Thus, zenithal openings of the natural light pipes type can be adopted as a preventive strategy for the adequate availability of daylighting in social housing that can be self-construction. In this sense, this research aims to analyze the lighting performance of natural light pipes in the kitchen environment of a single-family housing of social interest. The methodology was divided into three phases, namely: in Phase 1 (20 models) it was possible to analyze the availability of daylight in the internal environment, coming from natural light pipes, as well as the influence of the addition of elbow, variation of the inclination and increase in the length and dimension of the tube section. In Phase 2 (5 models), based on a case study, the lighting performance of a kitchen model was analyzed, with or without construction changes, recurrent in single-family housing of social interest. Subsequently, the kitchen model whose results indicate greater lighting losses due to self construction, the models of natural light pipes that present better performances in Phase 1 are inserted. The simulations performed in the Troplux 8 software verify the indexes of UDI (Useful Daylight Illuminance), sDA (Spatial Daylight Autonomy), ASE (Annual Sunlight Exposure), EMA (Average Annual Illuminance), UR (Daylight Uniformity Ratio) and Isocurves. Among the models analyzed, the results obtained for “M5/F1[69°/1.2x0.2m/J]” and “M15/F1[69°/1.2x0.4m/J]” stand out, both have a length of 1.2 m, with elbow and the same inclination (69°). A larger dimension of the tube section in “M15/F1[69°/1.2x0.4m/J]”, when compared to “M5/F1[69°/1.2x0.2m/J]”, contributed to the increase in EMA values by 38% to 128%, with this change being more effective in the winter months. The insertion of these models of natural light pipes into the kitchen model with the addition of a garage and adjoining room attests to the ability of these systems to contribute to a better availability of daylight in the internal environment, as well as preventing the decay of internal illuminance to levels below those recommended by NBR 15575-1 (ABNT, 2013), in cases where obstructions of conventional openings occur due to self-construction.